Syed Sheikh al-Hadi’s views on the educational reforms in Malaya - Akgun, Tayfun; Hafiz Zakariya (Penerbit Universiti Kebangsaan Malaysia, 2019)
Though there is a growing body of literature on Syed Sheikh al-Hadi, few focuses on his contributions to the educational reform. Thus, this study analyzes Syed Sheikh al-Hadi’s views on the educational reforms. Al-Hadi was discontent with the traditional Islamic education in Malaya because of its inadequacy to prepare the future generation to meet the challenges of modernity. For this purpose, al-Hadi emphasized the reform of Islamic education system through the madrasah, which would offer both the religious and secular subjects. Further, al-Hadi proposed the Malay-Anglo school: integrating the positive elements of the Malay school with the English school for the benefits of the Malay students. In order to revitalize the society, al-Hadi emphasized that women’s education needed to be addressed urgently. Besides contributing to theoretical discussion, al-Hadi was also involved in various capacities in the establishment and management of several madrasahs: Madrasah Iqbal Islamiah, Madrasah al-Hadi dan Madrasah al-Masyhur. This study adopts the textual study approach in examining the relevant primary sources. At the same time, it connects the text with the larger socio-historical contexts, which shaped the production of ideas and text.